Identification of the Novel Effector RsIA_NP8 in Rhizoctonia solani AG1 IA That Induces Cell Death and Triggers Defense Responses in Non-Host Plants - Wei, Miaomiao; Wang, Aijun; Liu, Yao; Ma, Li; Niu, Xianyu; Zheng, Aiping (Frontiers in Microbiology, 2020)
Rhizoctonia solani AG1 IA is a necrotrophic fungus that causes rice sheath blight, one of the most significant rice diseases in the world. However, little is known about the pathogenic mechanisms and functions of effectors in R. solani AG1 IA. We performed functional studies on effectors in R. solani AG1 IA and found that, of 11 putative effectors tested, only RsIA_NP8 caused necrosis in the leaves of Nicotiana benthamiana. The predicted signal peptide of this protein was required to induce cell death, whereas predicted N-glycosylation sites were not required. RsIA_NP8 was upregulated during early infection, and the encoded protein was secreted. Furthermore, the ability of RsIA_NP8 to trigger cell death in N. benthamiana depended on suppressor of G2 allele of Skp1 (SGT1) and heat shock protein 90 (HSP90), but not on Mla12 resistance (RAR1) and somatic embryogenesis receptor-like kinase (SERK3). A natural variation that prevents the triggering of cell death in N. benthamiana was found in RsIA_NP8 in 25 R. solani AG1 IA strains. It is important to note that RsIA_NP8 induced the immune response in N. benthamiana leaves. Collectively, these results show that RsIA_NP8 is a possible effector that plays a key role in R. solani AG1 IA–host interactions.